Self-Image and Suicide in a Swedish National Eating Disorders Clinical Register - Runfola, Cristin D. (2013)
OBJECTIVE: Using a prospective design, to examine the relation between self-image (assessed using the Structural Analysis of Social Behavior) and suicide attempts/completions in women with anorexia nervosa-restricting type (ANR), anorexia nervosa-binge/purge type (ANBP), bulimia nervosa (BN), binge eating disorder, and eating disorder not otherwise specified (EDNOS); and to assess whether these self-image variables add unique predictive value to suicide when considering other baseline predictors. METHOD: Women (N=2,269) age 12 to 45 (M=22.1) presenting to specialist eating disorders clinics in Sweden between 2005 and 2009 were identified through the Stepwise Eating Disorders Quality Register. Data on age, body mass index, eating disorder severity (Eating Disorder Examination-Questionnaire scores), psychiatric comorbidity, global assessment of functioning, and self-image were abstracted from Stepwise and included as baseline predictors or covariates. Suicide information (prior attempt and attempt/completion after Stepwise registration) was obtained from the National Patient Register and Cause of Death Register. RESULTS: Prevalence of detected suicide attempts/completions over the study period was 9.2%. Negative self-image variables were associated with prior suicide attempts in ANR and EDNOS and later suicide attempts/completions in women with BN. In a stepwise Cox proportional hazards model, only low self-affirmation predicted time to suicide attempts/completions in women with BN when accounting for age and prior suicide attempt. CONCLUSION: Assessing self-image might assist with identifying women with BN at elevated risk for suicide.